Successful Integration of Clinical Pharmacists in an OPAT Program: A Real-Life Multidisciplinary Circuit - Sara Ortonobes; Abel Mujal-Martínez; María de Castro Julve; Alba González-Sánchez; Rafael Jiménez-Pérez; Manuel Hernández-Ávila; Natalia De Alfonso; Ingrid Maye-Pérez; Teresa Valle-Delmás; Alba Rodríguez-Sánchez; Jessica Pino-García; Mònica Gómez-Valent (MDPI AG, 2022)
Outpatient parenteral antimicrobial therapy (OPAT) programs encompass a range of healthcare processes aiming to treat infections at home, with the preferential use of the intravenous route. Although several barriers arise during the implementation of OPAT circuits, recent cumulative data have supported the effectiveness of these programs, demonstrating their application in a safe and cost-effective manner. Given that OPAT is evolving towards treating patients with higher complexity, a multidisciplinary team including physicians, pharmacists, and nursing staff should lead the program. The professionals involved require previous experience in infectious diseases treatment as well as in outpatient healthcare and self-administration. As we describe here, clinical pharmacists exert a key role in OPAT multidisciplinary teams. Their intervention is essential to optimize antimicrobial prescriptions through their participation in stewardship programs as well as to closely follow patients from a pharmacotherapeutic perspective. Moreover, pharmacists provide specialized counseling on antimicrobial treatment technical compounding. In fact, OPAT elaboration in sterile environments and pharmacy department clean rooms increases OPAT stability and safety, enhancing the quality of the program. In summary, building multidisciplinary teams with the involvement of clinical pharmacists improves the management of home-treated infections, promoting a safe self-administration and increasing OPAT patients' quality of life.